Production Cost Efficiency and Profitability of Abakaliki Rice in Ihialia Local Government Area of Anambra State, Nigeria - J Egbodion; J Ahmadu (Journal of Applied Sciences and Environmental Management)
The study focused on the production cost efficiency and profitability of Abakaliki rice in Ihialia Local Government Area of Anambra State, Nigeria.. A random sampling technique was employed to select a total of 100 Abakaliki rice farmers from the study area. Data collection was achieved through the administration of structured questionnaire assisted with personal interview. Data analysis was done using descriptive statistics, gross margin analysis and stochastic frontier cost function. The results of the study showed that the Abakaliki rice production was profitable with average gross margin, net profit and return per naira invested of N141,607.22/ha, N126,056.33/ha and 3.54 respectively. With the exception of depreciation and output of rice, all the variables under consideration had positive and significant effect on the total cost of rice production. They were all significant at 5% level of probability. The farmers had cost efficiency ranging from 1.001 - 1.122 with the average of 1.048. Majority (90%) of them had efficiency range close to the frontier (1.001 - 1.100). Since the Abakaliki rice production was profitable and there was high level of cost efficiency, the farmers should be encouraged to expand their holdings and boost rice production.